Inhibitory Effects of Porphyra tenera Extract on Oxidation and Inflammatory Responses - Lee, Chul Won (Evid Based Complement Alternat Med, 2021)
Porphyra tenera (laver) has long been a popular and traditional seaweed food in Korea, Japan, and China. Historically, it was known as a marine medicinal herb to treat hemorrhoids and cholera morbus in Donguibogam. We investigated the effects of P. tenera extract (PTE) for its antioxidant and anti-inflammatory activities. These activities were measured using assays for 2,2-diphenyl-1-picrylhydrazyl (DPPH) and nitric oxide (NO) radical scavenging and its superoxide dismutase- (SOD-) like activity, and through the inhibitory production of inflammatory mediators (prostaglandin E(2) (PGE(2)), NO, tumor necrosis factor alpha (TNF-α), and interleukin-6 (IL-6)) in lipopolysaccharide- (LPS-) stimulated Raw 264.7 cells. The antioxidant assay results showed that PTE displayed DPPH radical scavenging activity (46.44%), NO radical scavenging activity (67.14%), and SOD-like activity (80.29%) at a concentration of 5 mg/mL. In the anti-inflammatory assays, treatment with PTE (1 mg/mL) significantly inhibited expression levels of LPS-induced COX-2 and iNOS, as well as the production of PGE(2), NO, TNF-α, and IL-6. These results show that PTE has antioxidant and anti-inflammatory properties and provide scientific evidence to explain the antioxidative and anti-inflammatory properties of PTE.